Progressivism Learning Management in Early Childhood Education: A Strategy for Developing Independence and Creativity in Early Childhood - Sulistiawati, Sulistiawati (CV. Creative Tugu Pena, 2025)
This study examines the implementation of progressivism-based learning management as a strategic approach to developing independence and creativity in early childhood within PAUD institutions in Tulang Bawang. Using a qualitative case study design, data were collected through participatory observation, in-depth interviews with principals and teachers, and documentation analysis. The findings reveal that learning management grounded in progressivism principles—child-centered planning, experiential implementation, and authentic evaluation—effectively fosters children’s autonomy and creative capacity. Planning is characterized by flexible, interest-driven curriculum design that integrates local cultural elements, while classroom practices emphasize open-ended exploration, project-based activities, and facilitative teacher–child interactions. Evaluation shifts from product-oriented assessment to continuous, process-focused documentation through portfolios and learning stories. The integration of local materials and cultural context enriches learning experiences, demonstrating that progressivism can be adapted meaningfully in rural settings with limited resources. This study contributes to theoretical and practical insights by providing a holistic model of progressive learning management and highlighting the symbiotic relationship between independence and creativity. Despite challenges related to teacher understanding and facility limitations, strong stakeholder commitment supports sustainable implementation. These findings offer a contextual model that can be adopted by other regions aiming to advance progressive early childhood education aligned with local values.